Determination of meropenem in serum by high-performance liquid chromatography with column switching - Bompadre, S; Ferrante, L; De Martinis, M; Leone, L (Journal of Chromatography A, 1998)
A rapid, accurate and sensitive liquid chromatographic assay with on-line solid-phase extraction for determination of meropenem in serum is described. Sample was directly injected onto the extraction column for sample clean-up and extraction. Thereafter, using an on-line column-switching system the drug was quantitatively transferred and separated on a C 18 analytical column. Ultraviolet absorption at 298 nm was used for detection. The assay was linear from 1 to 100 μg/ml. Recovery was 98.5%. Based on a 20-μl sample volume (serum–water, 1:1, v/v), detection limit was 0.1 μg/ml. An application of the method to study the pharmacokinetics of meropenem is given.